Pasión por enseñar : la identidad personal y profesional del docente y sus valores - Day, Christopher, 1943- (Educadores XXI, 2014)
This book is a celebration and an acknowledgement of the various forms of intellectual, physical, emotional and in particular passionate endeavour in which teachers at their best engage.